Teacher’s Strategies in Teaching Listening - Sherly Argisila; Nani Lestari Situmorang; Monika Br Boangmanalu (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
In the teaching and learning process, listening is not just a difficult skill to learn but also has its own challenge to be taught, therefore the researcher tries to carried out the strategy used by the English teachers in teaching listening especially for grade 9th students at SMP Nurcahaya Medan. The method was used in this study was qualitative method. Two English teachers were selected to be the participant in the class observing, not-taking and strustured-interview instruments. The result of the study showed that the biggest difficult in listening in the class, came from the students which think that listening wasn’t attractive, and to solved it, the English teachers used some strategies like, applying the note taking, summarizing, and also the pay attention strategies. The teachers also upgrade the creative media for listening and persuasive students to doing the listening practice.